Analisis Kelengkapan Pengisian Rekam Medis Pada Poliklinik Rawat Jalan Bedah Di Rs Pertamina Bintang Amin - Dwi Robbiardy Eksa; Neno Fitriyani Hasbie; Achmad Farich; Dinda Ayu Pratiwi (Malahayati Nursing Journal, 2021)
ABSTRACT: ANALYSIS OF COMPLETENESS OF MEDICAL RECORDING IN THE POLYCLINIC OF SURGICAL AT THE PERTAMINA BINTANG AMIN Backrgound: Medical records contain all information about patients, illness, medications and records in it recording to the order of service / care. There are still some an inadequate medical records. This happens because of the short time factor, the levels of doctor’s knowledge, and human resources.Purpose: this study was to determine the frequency distribution of completing medical record filling in outpatient surgical polyclinics at Pertamina Bintang Amin Hospital in 2019.Method: This type of research is a descriptive study with a cross sectional approach. Regarding the analysis of the completeness of filling in medical records, the research subject was an outpatients surgical polyclinic at Pertamina Bintang Amin Hospital in 2019. The research time was August-October 2020 with a sample of 400 medical records.Result: It was found that 73,5% outpatient surgical medical records were completely filled, 9,5% less complete and 17% incomplete. The frequency distribution of the components of completing medical record filling consisted of 98,75% complete and 1,25% incomplete identify, complete date and time 90% and 1% incomplete, history 94,25% complete and 5,75% incomplete, the result of physical and supporting examinations 87,5% complete and 12,5% incomplete, diagnosis 97,5% complete and 2,5% incomplete, treatment or action 94,74% complete and 5,26% incomplete, other services provided to patients 83,5% are complete and 16,5% incomplete, consent to action if necessary 88,75% complete and 11,25% incomplete. Ant the frequency distribution of components that are considered less complete is the filling of the management plan 76,26%, all anesthesia during pre and post surgery 79,5%, all surgery reports (pathology and postoperative progress notes) 79,75%, all reports of recorvery room 66,75%. The frequency distribution of completing medical record filling in outpatient surgical polyclinics at Pertamina Bintang Amin Hospital is 73,5% completely filled, 9,5% less complete, and 17% complete.Conslusion: This shows that the result of completingthe filling of medical records at the outpatient surgical clinic at Bintang Amin Hospital are still less complete. Keywords: Completeness, Medical Record, Surgical Polyclinic    INTISARI: ANALISIS KELENGKAPAN PENGISIAN REKAM MEDIS PADA POLIKLINIK RAWAT JALAN BEDAH DI RUMAH SAKIT PERTAMINA BINTANG AMIN Pendahuluan: Rekam medis berisi semua informasi mengenai pasien, penyakit, pengobatan dan rekaman yang didalamnya sesuai dengan urutan pelayanan/perawatan. Masih ditemukan beberapa rekam medis yang tidak memenuhi syarat. Hal tersebut terjadi karena beberapa faktor  waktu yang singkat, tingkat pengetahuan dokter dan sumber  daya manusia.Tujuan: penelitian ini bertujuan untuk mengetahui distribusi frekuensi kelengkapan pengisian rekam medis pada poliklinik rawat jalan bedah di Rumah Sakit Pertamina Bintang Amin Tahun 2019.Metode: Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan cross sectional. Mengenai analisis kelengkapan pengisian rekam medis, dengan subjek penelitian adalah poliklinik rawat jalan bedah di Rumah Sakit Pertamina Bintang Amin Tahun 2019 dengan jumlah sampel rekam medis sebanyak 400. Hasil: Didapatkan kelengkapan rekam medis poliklinik rawat jalan bedah sebanyak 73,5% terisi lengkap, 9,5% kurang lengkap dan 17% tidak lengkap. Distribusi frekuensi kelengkapan pengisian rekam medis poliklinik rawat jalan bedah di Rumah Sakit Pertamina Bintang Amin tahun 2019 tertinggi terdapat pada komponen tanggal dan waktu yaitu 99% lengkap dan komponen terendah terdapat pada semua laporan ruang pemulihan (recovery room) yaitu 66,75%. Distribusi frekuensi kelengkapan rekam medis poliklinik rawat jalan bedah di Rumah Sakit Pertamina Bintang Amin sebanyak 73,5% terisi lengkap, 9,5% kurang lengkap dan 17% tidak terisi lengkap.Kesimpulan: Hal ini menunjukkan hasil kelengkapan pengisian rekam medis pada poliklinik rawat jalan bedah Rumah Sakit Bintang Amin masih kurang lengkap. Kata Kunci : Kelengkapan, Rekam Medis, Rawat Jalan Bedah